Award-winning tool leverages agrobiodiversity for sustainable food systems - Jones, Sarah K. (CGIAR System Organization, 2023)
“The food system is at the center of multiple challenges that we’re facing. This includes the biodiversity crisis, the climate crisis, the malnutrition crisis, and a crisis of growing inequity. Within the food system, the entire supply chain depends on agrobiodiversity – the plants, animals, and microorganisms that support food and agriculture – and we’re not paying attention to its importance. We need to do more to eat it, use it, and save it in ways that catalyze the transition to a sustainable food system.” – Sarah Jones, co-creator of the Agrobiodiversity Index